The NF-κB RelA transcription factor is not required for CD8+ T-cell function in acute viral infection and cancer - Voisin, Allison; Plaschka, Maud; Perrin-Niquet, Marlène; Twardowski, Julie; Boutemine, Insaf; Eluard, Baptiste; Lalle, Guilhem; Stéphan, Pierre; Bouherrou, Khaled; Tonon, Laurie; Pommier, Roxane; Ferrari, Anthony; et al. (Frontiers in Immunology, 2024)
CD8 + T cells are critical mediators of pathogen clearance and anti-tumor immunity. Although signaling pathways leading to the activation of NF-κB transcription factors have crucial functions in the regulation of immune responses, the CD8 + T cell-autonomous roles of the different NF-κB subunits, are still unresolved. Here, we investigated the function of the ubiquitously expressed transcription factor RelA in CD8 + T-cell biology using a novel mouse model and gene-edited human cells. We found that CD8 + T cell-specific ablation of RelA markedly altered the transcriptome of ex vivo stimulated cells, but maintained the proliferative capacity of both mouse and human cells. In contrast, in vivo experiments showed that RelA deficiency did not affect the CD8 + T-cell response to acute viral infection or transplanted tumors. Our data suggest that in CD8 + T cells, RelA is dispensable for their protective activity in pathological contexts.